Constructed wetlands in China: recent developments and future challenges. Issue 5 (20th May 2008) - Liu, Dong; Ge, Ying; Chang, Jie; Peng, Changhui; Gu, Binhe; Chan, Gilbert YS; Wu, Xiaofu
Abstract : Constructed wetlands (CWs) are an emerging, environmentally friendly engineering system employed in China. They require lower investment and operation costs while providing higher treatment efficiency and more ecosystem services than conventional wastewater treatment methods. Introduced to China in 1987, CW systems used for wastewater treatment have rapidly increased in number, particularly since the late 1990s. This review summarizes the state‐of‐the‐art application of CW systems for water pollution treatment by reviewing the basics of the technology and its historical development and performance efficiency. Current progress, limitations, future concerns, and the challenges of CW technologies are also discussed. Also highlighted is the need for sufficient and appropriate data to assist in the further development of CW systems and the implementation of integrated "bottom‐up" and "top‐down" approaches by both the public in general and government bodies in particular.